Regulatory science and uncertainty in the risk assessment of pesticide residues - Diggle, Rebecca (2010)
In this thesis I examine how the scientific advisory system in England and Wales has responded to concerns about the risks of pesticide residues in food and demands for wider engagement in the formulation of advice. Specifically, I explore how the Advisory Committee on Pesticides (ACP) frames scientific uncertainties in risk assessment, and why some bodies outside and within government are critical of the ACP’s approach that is centred in the conventional single-chemical, high-dose-response paradigm of toxicology. Although some of these challenges date back to the early history of pesticide regulation in England and Wales, the emergence of scientific research employing different methods to assess the effects of chemical mixtures and chronic low-level exposure has stimulated new concerns about the risks posed by pesticide residues for human health.